(untitled) (IAHS Medical Journal, 2024)
Background: Severe preeclampsia and eclampsia are common in Bangladesh and are one of the leading cause of perinatal morbidity and mortality. The aim of the study is to observe the effect and hazards of intrathecal anesthesia for the mangement of caesarean section for severe pre-eclampsia and eclampsia patients. Management of these patients is very much important for the strenuous obstetrician and anesthesiologist both. Materials and Methods: This retrospective observational study was conducted in the Department of Anesthesiology and ICU of the IAHS (Institute of Applied Health Sciences) Chattogram from January 2022 to December 2022. Total 50 ASA grade 1 or 11, aged between 18-40 years, need urgent LSCS of 1-2 hours duration cases were selected purposively for intrathecal anesthesia. Patients with known cardiovascular and pulmonary diseases, fetal distress, severe maternal distress, uncontrolled DM, presence of any contraindication, patient’s refusal for SAB, septicemia, BP>170/120 mmhg, altered coagulation profile, APH, IUD were excluded from this study. Results: Among the study subjects, 30(59.68%) cases were primigravida patients- out of which five had severe pre eclampsia and 25 had eclampsia. Intraoperative shivering was observed in 18(29.03%) cases, postoperative shivering was observed in 16(25.80%) cases. Acute renal failure was found in 3(6%) cases, HELLP syndrome 10%, DIC 8%, abruption placentae 14%, pulmonary edema 4%, septicemia 16%, PPH 12% and postpartum eclampsia 22% cases. Apgar score <7 at 5 minutes in severe PET was observed in 04(6.45%) cases and eclampsia in 07 (14.51%) cases. Among them 10(20.96%) were eclamptic and 02(4.83%) had PET. p value was found 0.000 which is very highly significant. Conclusion: The outcome results of intrathecal anesthesia is better than general anesthesia. IAHS Medical Journal Volume 6(2) December 2023; 58-63